When can maximal efficacy occur with repeat botulinum toxin injection in upper limb spastic paresis? - Gracies, Jean-Michel; Jech, Robert; Valkovic, Peter; Marque, Philippe; Vecchio, Michele; Denes, Zoltan; Vilain, Claire; Delafont, Bruno; Picaut, Philippe (Brain communications, 2021)
Repeated injection cycles with abobotulinumtoxinA, a botulinum toxin type A, are recommended in current clinical guidelines as a treatment option for adults with upper limb spastic paresis. However, the magnitude of the maximal therapeutic effect of repeated abobotulinumtoxinA treatment across different efficacy parameters and the number of injection cycles required to reach maximal effect remain to be elucidated. Here, we present a post hoc exploratory analysis of a randomized, double-blind, placebo-controlled trial (12-24 weeks; NCT01313299) and open-label extension study (up to 12 months; NCT0131331), in patients aged 18-80 years with hemiparesis for ≥6 months after stroke/traumatic brain injury. Two inferential methods were used to assess the changes in efficacy parameters after repeat abobotulinumtoxinA treatment cycles: Mixed Model Repeated Measures analysis and Non-Linear Random Coefficients analysis. Using the latter model, the expected maximal effect size (not placebo-controlled) and the number of treatment cycles to reach 90% of this maximal effect were estimated. Treatment responses in terms of passive and perceived parameters (i.e. modified Ashworth scale in primary target muscle group, disability assessment scale for principal target for treatment or limb position, and angle of catch at fast speed) were estimated to reach near-maximal effect in two to three cycles. Near-maximal treatment effect for active parameters (i.e. active range of motion against the resistance of extrinsic finger flexors and active function, assessed by the Modified Frenchay Scale) was estimated to be reached one to two cycles later. In contrast to most parameters, active function showed greater improvements at Week 12 (estimated maximal change from baseline-modified Frenchay Scale overall score: +0.8 (95% confidence interval, 0.6; 1.0) than at Week 4 (+0.6 [95% confidence interval, 0.4; 0.8]). Overall, the analyses suggest that repeated treatment cycles with abobotulinumtoxinA in patients chronically affected with upper limb spastic paresis allow them to relearn how to use the affected arm with now looser antagonists. Future studies should assess active parameters as primary outcome measures over repeated treatment cycles, and assess efficacy at the 12-week time-point of each cycle, as the benefits of abobotulinumtoxinA may be underestimated in the studies of insufficient duration. Abbreviated summary In this post hoc analysis of repeated abobotulinumtoxinA injection cycles in upper limb spastic paresis, Gracies et al. used statistical modelling to elucidate the maximal therapeutic effect of abobotulinumtoxinA. Notably, the number of injections required to reach this maximal effect was higher for active (e.g. active function) compared with passive (e.g. tone) parameters.
Keywords: repeat injection; maximal effect; abobotulinumtoxinA; non‐linear random coefficient; upper limb spastic paresis